Using streptomyces as potential biocontrol agents against rhizoctonia solani causing root rot disease - Fatma Shams Lotfy Ali Mahmoud; Hussien Emam Makboul; Mohamed Abdallah Moselhy; Ayat Mahmuod El-Sayed (2025)
Rhizoctonia solani is a destructive soil-borne fungal pathogen which infects many important crops, including green beans. This work was conducted to isolate and screen the actinobacteria with potential biocontrol capacity against this phytopathgen. After screening, two isolates AC82 and AC143 were selected for further study according to their ability to reduce the mycelial growth of R. solani by antibiosis in dual culture. These two isolates were identified as Streptomyces lividans and Streptomyces rochei based on their morphological, and biochemical characteristics as well as 16S rRNA gene sequenceing. The antifungal mechanisms of both strains were seen through the light and SEM microspic images. Also, the selected strains could produce hydrolytic enzymes. The cultural and fermentation conditions for both strains were optimized by single-factor and response surface methods. The use of low-cost novel medium ingredients (molasses and CSL) greatly enhanced the antifungal activity of both strains. The overall suppression of R. solani growth reached 92 and 91% with an improvement of 53 and 68% for S. lividans and S. rochei, respectively, when compared to the basal medium. The Fourier transform infrared (FT-IR) spectra for both extracts revealed the varied patterns of functional groups absorption of the bioactive compounds (BACs). Moreover, LC-ESI-MS/MS [M-H]- analysis of the crude extracts revealed the presence of 22 and 21 diverse secondary metabolite compounds produced by S. lividans and S. rochei, respectively. A moderate antioxidant activity was noticed for S. lividans and S. Rochei. In addition, BACs from Streptomyces spp exhibited significant antibacterial activity. Streptomyces spp extracts showed a moderate level of cytotoxicity against lung cancer cell lines (A-549) with low cytotoxic effects on lung normal cell lines (WI-38). The greenhouse experiments revealed that the fermentation broth of both strains increased the percentages of surviving green bean plants (75-80%) in comparison to control (25-30%). Using a mix of both strains supported surviving 86.1 and 90.6% of bean plants compared with 31.1 and 48.3% in control treatments, in the commercial greenhouses located in Giza and Ismailia Governorates. The biological activities of both Streptomyces extracts might be attributed to the presence of a variety of metabolites, and hence, two Streptomyces strains can be used as an excellent source for bioactive compounds and as promising biocontrol agents in R. solani management.
Rhizoctonia solani(3gh eSHH eQVi aWQi eeQV jfJbd Yf WQjb GdJQHI hjUjH GdYOjO ef GdeMGUjd GdgGeI, HeG aj Pdc GdaGUhdjGA GdNVQGA(B. (3Je ELQGA gPG GdYed dYRd haMU GdBcJjfhHcJjQjG PGJ GdbOQI Ydi GdecGaMI GdMjhjI VO gPG GdeSHH GdeQVj ddfHGJ(B. (3h HYO GdaMU GdChdj, Je GNJjGQ GdYRdJjf (BAC82 (3h(BAC143 (3deRjO ef GdOQGSI hakbG dbOQJgeG Ydi JKHjW Gdfeh GdaWQj d` (BR. solani (3Yf WQjb BdjI GdJVGO GdMjhj aj GdRQGYI GdeROhLI(B. (3Je JYQja gGJjf GdYRdJjf Ydi CfgeG(BStreptomyces lividans (3h(BStreptomyces rochei (3HfGAG Ydi GdNUGFU GdehQahdhLjI hGdHjhcjejGFjI , HGdEVGaI Edi JSdSd Ljf (BrRNA .16S(3Je OQGSI GdBdjGJ GdeVGOI ddaWQjGJ dcdJG GdSdGdJjf ef NdGd UhQ GdejcQhSchH GdVhFj hGdEdcJQhfj GdeGSM(B. (3ceG CKHJJ GdSdGdGJ GdeNJGQI bOQJgG Ydi EfJGL HYV GdEfRjeGJ GdNGQLjI GdeMddI(B. (3Je JMSjf GdXQha GdeRQYjI hGdJNejQjI dcdJG GdSdGdJjf HGSJNOGe WQb GdYGed GdaQOi h GdGSJLGHI GdSWMjI(B. (3cPdc COi GSJNOGe echfGJ HjFjI LOjOI efNaVI GdJcdaI eKd GdehdGS heSJNdU GdPQI GdSGFdI Edi JYRjR GdfTGW GdeVGO ddaWQjGJ dcdJG GdSdGdJjf HTcd cHjQ(B. (3HdZJ fSHI JKHjW feh (BR. solani (3GdELeGdjI Gdi (B92 (3h(B91% (3eY JMSf HfSHI (B53 (3h(B68% (3dSdGdJj (BS. lividans (3h(BS. rochei (3Ydi GdJhGdj ebGQfI HGdhSW GdHjFi GdCSGSj(B. (3cTaJ CWjGa JMdjd GdCTYI JMJ(B(FT-IR) (3dcdG GdeSJNdUjf Yf GdCfeGW GdeJfhYI dGeJUGU GdeLehYGJ GdhXjajI ddeQcHGJ GdMjhjI GdfTWI (B(BACs) (3HGdEVGaI Edi Pdc, cTaJ JbfjI JMdjd (BLC-ESI-MS/MS [M-H]- (3Yf hLhO (B22 (3h(B21 (3eQckHG KGfhkjG eJfhkYG efJLI HhGSWI SdGdJj (BS. lividans (3h(BS. rochei (3Ydi GdJhGdj(B. (3Je JSLjd fTGW eJhSW eVGO ddCcSOI d`cd ef (BS. lividans (3h(BS. rochei. (3HGdEVGaI Edi Pdc, CXgQJ GdeQcHGJ GdHjhdhLjI GdfTWI (BBACs (3GdefJLI ef (B.Streptomyces spp (3fTGkWG eVGkOG ddHcJjQjG HTcd cHjQ VO eSHHGJ GdCeQGV GdHTQjI GdNWjQI(B. (3CXgQJ eSJNdUGJ (BStreptomyces spp. (3JCKjQ eJhSW ef GdSejI GdNdhjI VO NdGjG SQWGf GdQFI (B(A-549) (3eY JCKjQGJ efNaVI GdSejI Ydi NdGjG GdQFI GdWHjYjI (B.(WI-38) (3cTaJ JLGQH GdUhHI Cf SGFd GdJNejQ dcdJG GdSdGdJjf RGO ef fSHI HbGA fHGJGJ GdaGUhdjGA GdNVQGA HfSHI JJQGhM Hjf (B(75-80%) (3ebGQfI HGdeYGedI GdcfJQhd (B(25-30%). (3hYfO GSJNOGe NdjW ef cdJG GdSdGdJjf, hUdJ fSH HbGA GdfHGJGJ Edi (B86.1% (3h(B90.6% (3ebGQfI H`(B31.1 (3h(B48.3% (3aj GdeYGedGJ GdcfJQhd aj GdUhHI GdRQGYjI GdJLGQjI GdhGbYI aj eMGaXJj GdLjRI hGdESeGYjdjI Ydi GdJhGdj(B. (3jecf Cf oJYRi GdCfTWI GdHjhdhLjI dcdG eSJNdUj(BStreptomyces (3Edi hLhO eLehYI eJfhYI ef GdeQcHGJ GdKGfhjI, hHGdJGdj, jecf GSJNOGe SdGdGJi (BStreptomyces (3ceUOQ eeJGR ddeQcHGJ GdfTWI HjhdhLkjG hcYhGed ecGaMI MjhjI hGYOI aj GdbVGA Ydi aWQ (BR. solani.s
Thesis (Ph.D)-Cairo University, 2025.
Bibliography: pages 145-181.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Fungal diseases; (3GdGeQGV GdaWQjI s; Antifungal activity -- Rhizoctonia solani -- Streptomyces -- Optimization -- Biological control -- Antimicrobial activity -- Antioxidant activity